Synthesis of Acetylene Black and Polyvinylidene Difluoride to Improve the Conductivity of Li-ion Nickel Manganese Cobalt Batteries - Totok Dermawan; Agus Sudjatno; Edy Yulianto; Yustinus Purwamargapratala; Suroso Suroso; Budi Suhendro; Ign Agus Purbhadi Wirgiyanto (Universitas Muhammadiyah Magelang, 2025)
The issue of low cathode conductivity is a significant challenge in battery development, particularly for automotive applications. The cathode plays a crucial role in Li-ion batteries, as it is responsible for transferring lithium ions during both charging and discharging processes. Therefore, this study aims to enhance the conductivity of the cathode by incorporating Acetylene Black (AB) and Polyvinylidene Difluoride (PVDF) additives. In this study, Nickel Manganese Cobalt (NMC) 811 and NMC 111 cathodes were used. These materials were formed into pellets, then made into sheets, with AB and PVDF additives added in a weight composition ratio of 85:10:5, and a coating thickness of 300 Âµm. The cathode conductivity was characterized using an LCR meter, while surface morphology, cross-section, EDS, and mapping of the cathode surface were analyzed with SEM. The results showed that the addition of additives increased the conductivity of NMC 111 by more than five times, from 23.27x10-8 S.cm-1 to 119.34x10-8 S.cm-1, and NMC 811 by more than twelve times, from 6.43x10-8 S.cm-1 to 81.79x10-8 S.cm-1. These findings suggest that higher particle density, improved size distribution, and smaller particle grains contribute to higher conductivity.